Factors Associated With Receiving Longer Than Recommended Therapy Among Culture-Negative Pulmonary Tuberculosis Patients. (21st November 2022) - Tsang, Clarisse A; Patel, Neha N; Stout, Jason E; Fernando, Robyn; Pratt, Robert; Goswami, Neela D
Abstract: Background: US tuberculosis (TB) guidelines recommend treatment ≥6 months with a regimen composed of multiple effective anti-TB drugs. Since 2003, a 4-month regimen for a specific subset of TB patients has also been recommended. Methods: We used 2011–2018 US National Tuberculosis Surveillance System data to characterize factors associated with 4-month (111–140 days) therapy among adult patients who had completed treatment and were potentially eligible at that time for 4-month therapy (culture-negative pulmonary-only TB, absence of certain risk factors, and initial treatment that included pyrazinamide). We used modified Poisson regression with backward elimination of main effect variables to calculate adjusted relative risks (aRRs). Results: During 2011–2018, 63 393 adults completed TB treatment: 5560 (8.8%) were potentially eligible for 4-month therapy; of these, 5560 patients (79%) received >4-month therapy (median, 193 days or ∼6 months). Patients with cavitary disease were more likely to receive >4-month therapy (aRR, 1.10; 95% CI, 1.07–1.14) vs patients without cavitary disease. Patients more likely to receive 4-month therapy included patients treated by health departments vs private providers only (aRR, 0.94; 95% CI, 0.91–0.98), those in the South and West vs the Midwest, non-US-born persons (aRR, 0.95; 95% CI, 0.91–0.99) vs US-born persons, and aged 25–64 years vs 15–24 years. Conclusions: Most patients potentially eligible for 4-month therapy were treated with standard 6-month courses. Beyond clinical eligibility criteria, other patient- and program-related factors might be more critical determinants of treatment duration. Abstract : Most culture-negative pulmonary tuberculosis patients potentially eligible for 4-month therapy in the United States were treated with longer courses. These analyses indicate that certain patient- and program-related factors might affect treatment duration.